PELATIHAN E-MODUL INTERAKTIF BERBASIS TEKNOLOGI INFORMASI UNTUK MENINGKATKAN LITERASI DIGITAL BAGI GURU - Subarkah, Pungkas; Prasetyo Kartika, Nur Kholifah Dwi; Rofiqoh, Dayana; Arsi, Primandani; Marcos, Hendra (Jurnal Abdi Nusa, 2024)
Mastering information technology, especially in the field of education for a teacher in the current era, is indeed a must that must be owned by each individual teacher. For this reason, professional flip pdf application training is needed to improve the ability to collaborate on more interactive learning media for students, for teachers of MI Muhammadiyah Wangon, Banyumas Regency. The purpose of this training is to provide knowledge and skills for teachers in optimizing information technology, especially the professional flip pdf application to support improving the ability to collaborate learning methods for students. The implementation method used is the Community Language Learning (CLL) method which consists of the preparation stage, implementation stage and evaluation stage. The results of this service during the training were active participant participation and the results obtained with the pre-test and post-test, then out of 15 participants, 97% of the trainees experienced an increase in their ability to use the professional flip pdf application. This activity is expected to contribute to efforts to improve information technology skills among teachers, especially in supporting teaching and learning activities for students to make them more interactive